Impact of Influencers in Consumer Decision-Making: The Fashion Industry - Siti Nurfadila; Setyo Riyanto (INTERDISCIPLINARY JOURNAL ON LAW, SOCIAL SCIENCES AND HUMANITIES, 2020)
The popularity of influencers is continuous and doesn’t have a limited window of influence. Internet and social media play vital role in helping consumers find the items they are looking for. Obviously companies will keenly try to retain a strong presence in the social media platforms; otherwise the target audience can easily change suppliers. The present study is intended to explore the influencer marketing techniques used by fashion industries and also the impact of influencers on the consumers buying decision process in fashion industry.